Institutional Analysis of Independent During Pandemic Era in Sleman Regency, Special Region of Yogyakarta - Gerry Katon Mahendra; Nur Faidati (JIP (Jurnal Ilmu Pemerintahan) : Kajian Ilmu Pemerintahan dan Politik Daerah, 2021)
This paper intends to This study focuses on independent tourism village institutions during pandemic era in Sleman Regency, Special Region of Yogyakarta. The research method used in this research is qualitative research methods. This research was conducted in 10 Independent Tourism Villages in Sleman Regency, between August - December 2020. In this study, three data collection techniques were used, including: literature study, interviews and documentation. Of the 10 tourist villages, 5 of them have sufficiently good institutions and are able to adapt to a pandemic situation. Meanwhile, the other 5 are not sufficiently well-institutionalized and capable of adapting to the pandemic situation. Tourist villages that are able to adapt are able to innovate in realizing quality tourism that pays attention to safety and health aspects through Cleanliness, Health, Safety and Environmental Sustainability (CHSE)